Living Qur’an, Gender, and Sibaliparriq, in Mandar, Indonesia: Cultural Construction in the Perspective of Islamic Law - Yakub, Bahruddin Umar; Husain, Husain; Nurdin, Abidin; Nurhayati, Nurhayati; Hidayatulloh, Miftah Khilmi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Cultural construction creates an unequal understanding of gender between men and women. This construction causes women to live in marginal and unfair conditions. This article aims to examine the concept of sibaliparriq in the construction of Mandar culture as associated with the living Qur'an. This study is a qualitative study using the Living Al-Qur'an approach and is analyzed using gender theory and the sociology of Islamic law. Data was collected through interviews, observation, and a literature review. This research finds that sibaliparriq, in the concept and application of Mandar, is a woman's willingness to help her husband in the household. Sibaliparriq is interpreted as affection (siasayanni), caring (siamanaoang pa'mai), brotherhood (palluluareang), and sincerity (sukku' mattulung). Sibaliparriq is related to the concept of gender in the Qur'an, and there is no contradiction between them, so that the cultural construction is also equal and balanced. Both position women in an honorable and dignified manner; they are seen as Allah's creatures who live to help each other; the difference between the two is only in piety (taqwa). Sibaliparriq is an application of the living Qur'an which is practiced in the life of the Mandar people, namely helping each other (ta’awūn) for good in household life. Sociologically, this has implications for Islamic and customary laws that are well integrated into society.